Caracterização nutricional da torta de moringa (Moringa oleifera Lam.) - Alves, Francyelle Gurgel de Castro (2018)
Moringa is an oleaginous plant that presents productive potential in the Brazilian northeast due to its good adaptability in regions with semi - arid climate and ease of propagation by different methods of planting. The oil extracted from the moringa seed has high resistance to oxidation and contains a high content of unsaturated fatty acids, which favors its industrial use. From this extraction, a residue with no economic value is obtained, which has nutritional characteristics that evidence the possibility of its use in animal feeding. The objective of this experiment was to evaluate the nutritive value of moringa (TM) cake through the chemical composition and fractionation of nitrogen compounds and total carbohydrates, and to verify the effects of increasing levels of moringa cake, replacing the cotton cake. from the determination of nutrient intake, digestibility coefficient and N balance of these nutrients. The chemical composition of the TM was determined according to the AOAC protocol and the fractionation according to the recommendation of the Cornell Net Carbohydrate and Protein System (CNCPS). For determination of intake, digestibility and N balance, five uncastrated male sheep, with a mean weight of 23.4 ± 1.4 kg, were distributed in a Latin square delineation, where the animals were allocated in individual metabolic cages and submitted to diets with different inclusion levels of TM. The experimental period lasted 65 days, starting with a 15-day adaptation period, followed by five homogeneous periods, each containing five days of adaptation to the diet and 5 days for collection of leftovers, faeces and urine. Consumption was counted daily from the tenth day of the adaptation period. The experimental rations were composed of hay of Tifton grass (Cynodon spp.), Milled grain corn, cotton pie (Gossypium hirsuntum L.) and moringa pie, alternating the percentage of the latter in proportions 0; 7.5; 15; 22.5 and 30%. The chemical composition determined 92.65% MS; 95.33% MO; 30.16% PB; 18.68% EE; 46.49% CHT; 17.42% CNF; 32.17% FDN; 25.41% FDA; and 8.36% LIG. The total carbohydrates were fractionated in the portions A ', B1', B2 'and C', with each fraction, respectively, 14.79%; 22.67%; 19.12% and 43.42%. The percentages of the nitrogen fractions A, B1 + B2, B3 and C found were: 32.81%; 20.31%; 24.43% and 22.57%. The inclusion of TM did not alter the intake of MS, OM, PB, PIDN, NDF, FDA, CHT, HEM and LIG, with the respective values of 800.78 g day-1; 726.90 g dia-1; 123.55 g dia-1; 45.65 g dia-1; 448.20 g dia-1; 231.49 g dia-1; 592.03 g dia-1; 105.34 g dia-1; 52.84 g dia-1. The consumption of PIDA, EE and CNF showed a significant difference, resulting in a directly proportional increase of EE to the inclusion of the pie in the diet, and indirectly proportional to the PIDA and CNF. There were no significant differences between 21 the digestibility coefficients of DM, OM, PB, EE, NDF, CHT and CNF with inclusion of moringa pie, obtaining, respectively, 57.33; 61.61; 42.42; 70.76; 40.40; 55.25 and 20.32%, which did not occur with the CDP, which evidenced a greater use of N from the increasing TM inclusion. The values of nitrogen balance (BN) presented similarity in the use of N by the animals. Therefore, the results showed that the moringa pie can be an alternative in the feeding of sheep according to their evaluated nutritional value